A Palladium‐Doped Graphitic Carbon Nitride Nanosheet with High Peroxidase‐Like Activity: Preparation, Characterization, and Application in Glucose Detection. (27th December 2017) - Jin, Xin; Zhong, Yingying; Chen, Lian; Xu, Liangjun; Wu, Yongning; Fu, FengFu
Abstract: Herein, a novel palladium‐doped graphitic carbon nitride nanosheet (g‐C3 N4 ‐PdNPs) is reported. The prepared g‐C3 N4 ‐PdNPs has a 6.7 and 14.0 times higher peroxidase‐like activity in comparison with pure Pd nanoparticles (PdNPs) and graphitic carbon nitride (g‐C3 N4 ) nanosheets respectively, and can be stably stored for 3 months. The high peroxidase‐like activity make g‐C3 N4 ‐PdNPs effectively catalyze H2 O2 ‐mediation oxidization of 3, 3, 5, 5′‐tetramethylbenzidine to generate a color change from colorless to blue under lower concentration level and shorter time. The g‐C3 N4 ‐PdNPs can be used as peroxidase mimetic to develop sensitive and specific colorimetric method for the rapid detection of glucose in the serum, and to fabricate a simple and cheap portable test kit for instrument‐free visual detection of glucose in serum. The portable test kit possesses obvious advantages such as low‐cost, short detection time, tiny sample consumption, excellent specificity, and higher visual sensitivity. The visual detection limit of portable test kit is lower than the glucose concentration in the serum of a diabetic. Using portable test kit, the glucose in serum can be visually detected by bare eye observation within 30 min with only 30 µL serum consumption. The success of this study provided a potential approach for low‐cost and instrument‐free "see" diabetes in clinical early diagnosis. Abstract : A novel palladium‐doped graphitic carbon nitride nanosheet, which possesses high peroxidase‐like activity and excellent stability, is prepared and used as peroxidase mimetic to fabricate sensitive and specific portable test kit for instrument‐free visual detection of glucose in serum samples.